Music, art, and metaphysics: Essays in philosophical aesthetics - Levinson, Jerrold (Oxford Oxford university press, 2011)
This is a long-awaited reissue of Jerrold Levinson's 1990 book Music, Art, and Metaphysics, which gathers together the writings that made him a leading figure in contemporary aesthetics. Most of the essays are distinguished by a concern with metaphysical questions about artworks and their properties, but other essays address the problem of art's definition, the psychology of aesthetic response, and the logic of interpreting and evaluating works of art. The focus of abouthalf of the essays is the art of music, the art of greatest interest to Levinson throughout his career. Many of the essays have been very influential, being among the most cited in contemporary aesthetics and having become essential references in debates on the definition of art, the ontology of art, emotionalresponse to art, expression in art, and the nature of art forms.